2020
DOI: 10.1111/coa.13614
|View full text |Cite
|
Sign up to set email alerts
|

Surgiflo®may have a potential impact on the healing process in cricotracheal resection anastomosis

Abstract: Objectives: To evaluate the role of thrombin-based haemostatic agent Surgiflo ® (Ethicon) in improving the outcome of cricotracheal resection anastomosis. Design: Randomised controlled clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Surgiflo is applied over the operative field and on the line of anastomosis. A study conducted by the authors of this work to assess the benefits of Surgiflo 27 revealed that our outcomes have improved significantly since adopting this procedure, specifically regarding the incidence of post-operative granulation tissue formation, anastomotic dehiscence, surgical emphysema, restenosis and overall success rates.…”
Section: Discussionmentioning
confidence: 97%
“…Surgiflo is applied over the operative field and on the line of anastomosis. A study conducted by the authors of this work to assess the benefits of Surgiflo 27 revealed that our outcomes have improved significantly since adopting this procedure, specifically regarding the incidence of post-operative granulation tissue formation, anastomotic dehiscence, surgical emphysema, restenosis and overall success rates.…”
Section: Discussionmentioning
confidence: 97%
“…Ma et al and EI-Fattah et al tested a thrombin-based hemostatic material (Surgiflo) in surgical patients separately. Both research groups showed that this material could successfully accelerate wound healing [ 16 , 18 ]. A meta-analysis that included six clinical trials reported another topical thrombin-based hemostatic agent (Floseal) that could also decrease the amount of bleeding and improve wound healing after total knee arthroplasty [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin is a serine protease and can regulate hemostasis [ 13 ]. Animal and clinical studies have demonstrated that thrombin-containing materials could improve surgical wound healing [ [14] , [15] , [16] , [17] ]. In a randomized controlled clinical trial, Ma et al reported that the topical application of a thrombin-containing matrix (Surgiflo) could successfully reduce the postoperative bleeding and amount of wound drainage after the posterior lumbar surgery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to conduct a prospective randomized controlled trial to evaluate the hemostatic e cacy and safety of prophylactic use of Surgi o™ compared to conventional hemostatic methods in patients undergoing treatment for LSS using PE-ULBD. Surgi o™ is able to quickly cover irregular wounds during application, demonstrating excellent hemostatic effects [24] . This study found that in terms of intraoperative coagulation time, the T group was signi cantly superior to the N group, and the T group had signi cantly lower perioperative blood loss compared to the N group, indicating that Surgi o™ has a more remarkable hemostatic effect.…”
Section: Discussionmentioning
confidence: 99%